Análise da dinâmica de secagem de pasta em leito de jorro - Silva, Carlos Adriano Moreira da (2016)
Although there are several mathematical models in the literature used for paste drying in spouted beds, few of them have focused on transient analysis of dynamic system. Therefore, the purpose of this study was to integrate experiments and simulations of a dynamic model to study the paste drying process in a spouted bed with inert particles. The tests were conducted to investigate the transient response by mean of experiments with disturbances and intermittences in the paste feed rates for understand the behavior of process during periods in which the equipment undergoes transients states. The experiments drying were performed in a spouted bed of cylindrical column of 50.0 cm of height and 20.0 cm of diameter for inlet gas temperatures of 70 °C and 100 °C and inlet spout air flow rate at 30% above the minimum spouting velocity. The paste used was a calcium carbonate suspension with solid concentration of 5 % w/w and glass spheres of 2,2 mm of average diameter used as inert particles. To describe the heat and mass transfer phenomena in the drying process was used semi-empirical models found in the literature. The models consist of an ordinary differential equations system coupled with an empirical equation to determine the water evaporation rate. For the numerical solution of the models, was developed a computer code based in Fortran 90 programming language using the DIVIPAG subroutine from IMSL library. Comparative analysis between experimental and simulated data were performed and it was verified that the adapted models represented good the paste drying process in the spouted bed under different conditions. The results obtained in this study showed good agreement with the behavior found in the literature and with the physical principles of momentum, heat and mass transfer involved in the process. This work contributed to a better understanding of the paste drying in spouted bed when the process goes by transit states due to disturbances and intermittences in the paste feed rates.